2020
DOI: 10.3390/app10196703
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Serious Game for Cognitive Training in Chronic Stroke Survivors with Mild-to-Moderate Cognitive Impairment: A Pilot Randomized Controlled Trial

Abstract: Previous cognitive training games for stroke survivors required the close supervision of therapists. We aim to demonstrate the preliminary therapeutic effectiveness of Neuro-World, serious mobile games for cognitive training, in chronic stroke survivors with mild-to-moderate cognitive impairment without therapist supervision. For that, we conducted a randomized, controlled clinical trial at a single long-term care rehabilitation center with 50 stroke survivors in the chronic stage with mild-to-moderate cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 69 publications
(88 reference statements)
0
25
0
Order By: Relevance
“…Computer-based interventions also make possible rehabilitation at the patient’s home, with indisputable logistical and psycho-emotional advantages. The use of technologies such as brain computer interfaces, robotics, virtual reality, and augmented reality tools currently adopted in the treatment of cognitive disorders in adult patients and children [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ] could also lead to indiscuss advantages in terms of motivation in posterior fossa tumor post-surgery rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-based interventions also make possible rehabilitation at the patient’s home, with indisputable logistical and psycho-emotional advantages. The use of technologies such as brain computer interfaces, robotics, virtual reality, and augmented reality tools currently adopted in the treatment of cognitive disorders in adult patients and children [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ] could also lead to indiscuss advantages in terms of motivation in posterior fossa tumor post-surgery rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The study utilized a hybrid model between ANOVA and Tukey's posthoc tests and found that all outcomes presented significant advancements except for language. Therefore, Neuro-World showed to enhance the cognitive function and decrease depression symptoms among the subjects in the intervention group [5].…”
Section: Serious Games and Attention (Cognitive Skills)mentioning
confidence: 92%
“…Thus, serious games show to improve memory and attention skills among the elderly. Similarly, in [5], the authors aimed to assess the value of "Neuro-World," a serious game, in cognitive training for stroke survivors who, as a result, present mild or moderate cognitive disabilities. The study utilized a hybrid model between ANOVA and Tukey's posthoc tests and found that all outcomes presented significant advancements except for language.…”
Section: Serious Games and Attention (Cognitive Skills)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the term Serious Games we are referring to games whose peculiarity is not mere entertainment, but the empowerment of cognitive and motor function [ 30 ]. Video games training for rehabilitative purpose has been widely validated both in motor rehabilitation [ 31 ] and in cognitive empowerment and rehabilitation in several disorders [ 32 , 33 , 34 ] ensuring a similar efficacy compared to conventional treatments.…”
Section: Developmental Coordination Disordermentioning
confidence: 99%